CREATIVE THINKING IN STUDENTS’ MATHEMATICAL COMMUNICATION IN SOLVING TWO-DIMENSIONAL GEOMETRY PROBLEMS: A COMMOGNITIVE PERSPECTIVE - Muhammad Rizal Usman; Sitti Rahmah Tahir; Dwi Aldi Hidayatulloh (JURNAL MathEdu (Mathematic Education Journal), 2026)
Mathematical communication skills and creative thinking are two essential aspects of mathematics learning; however, studies examining how creative thinking is manifested within mathematical communication remain limited. This study aims to describe how creative thinking is manifested in students’ mathematical communication when solving two-dimensional geometry problems from a commognitive perspective. This research employed a qualitative approach with a single-case study design. The research subject was one student who demonstrated a variety of strategies in solving contextual dua dimensi geometry problems. Data were collected through written tasks and semi-structured interviews, and were analyzed based on the components of commognitive discourse, namely the use of mathematical terms, visual representations, argumentative narratives, and solution patterns. The findings indicate that creative thinking is manifested through variations in representation, flexibility of strategies, originality in constructing arguments, and elaboration of mathematical explanations. These findings suggest that creativity can be identified through the structure of students’ mathematical communication and contribute theoretically to the integration of creativity within mathematical discourse analysis.